2021
DOI: 10.3390/ijerph182010680
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity Are Associated with Corresponding Changes in Psychological Well-Being: A Pandemic Case Study

Abstract: Societal crises and personal challenges are often followed by substantial changes in physical activity. Is there a link between such changes and psychological well-being? Seeking to answer this question, we conducted a correlational study on a representative sample in Sweden during the first year of the COVID-19 pandemic (N = 1035). About 49% of the sample had decreased their physical activity compared to their self-reported activity level prior to the pandemic, whereas 32% had increased it. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…However, women appear to have adapted to these changed circumstances and developed behavior to compensate for their loss of access to fitness centers by performing more non-organized activities, such as home-based exercises. This flexibility in types of PA performance may create opportunities to incorporate PA into daily living during the current pandemic and other social health-care crises, which is essential to improving well-being [ 12 ] and preventing lifestyle-related diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, women appear to have adapted to these changed circumstances and developed behavior to compensate for their loss of access to fitness centers by performing more non-organized activities, such as home-based exercises. This flexibility in types of PA performance may create opportunities to incorporate PA into daily living during the current pandemic and other social health-care crises, which is essential to improving well-being [ 12 ] and preventing lifestyle-related diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the pandemic, recent studies have demonstrated that PA plays an important role in reducing the impact of the COVID-19 pandemic because it increases resistance and reduces the risk of infectious diseases and mortality, in addition to enhancing vaccination outcomes [ 11 ]. PA during the pandemic is also associated with psychological well-being [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity can promote stress resilience [34] and serve as an effective coping strategy [11], including during the pandemic [35][36][37][38]. It is also effective at diminishing depressive symptoms as well as symptoms of other mental illnesses [39].…”
Section: Discussionmentioning
confidence: 99%
“…A survey was distributed on Facebook during the second week of April 2021, and a total of 1,788 Swedes (60% female, mean age 53.8 years, age range 19-85 years) anonymously filled out the questionnaire. Sweden has one of the world's highest social media penetrations, and previous research has found that Swedes are representative of how the COVID-19 pandemic has impacted people's subjective well-being (e.g., Dahlen et al 2021).…”
Section: Methodsmentioning
confidence: 99%